1999
DOI: 10.1001/archopht.117.8.1035
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Polypoidal Choroidal Vasculopathy in Japanese Patients

Abstract: To describe the vascular nature and clinical features of idiopathic polypoidal choroidal vasculopathy in Japanese patients.Methods: Patients thought to have idiopathic polypoidal choroidal vasculopathy were examined with binocular ophthalmoscopy, slitlamp biomicroscopy with a contact lens, fluorescein angiography, and indocyanine green angiography.Results: From January 1993 to December 1997, 35 eyes in 32 patients were diagnosed as having idiopathic polypoidal choroidal vasculopathy. Men were predominantly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
191
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 11 publications
13
191
1
Order By: Relevance
“…[11][12][13] This is in contrast to other series with predominantly Caucasian populations in which 15-47% were men. 14,15 It has been reported that 36% (5/14) of eyes with PCV and not treated had a worsening of visual acuity by 42 lines after a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[11][12][13] This is in contrast to other series with predominantly Caucasian populations in which 15-47% were men. 14,15 It has been reported that 36% (5/14) of eyes with PCV and not treated had a worsening of visual acuity by 42 lines after a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 84%
“…Despite its widespread use, Lafaut et al 14 reported unfavourable results of direct laser treatment for PCV due to a worsening of macular exudation after the treatment. A long-term follow-up study of eyes treated with laser photocoagulation targeting only polypoidal lesions showed bleeding and exudation from recurrent polypoidal lesions at the edges of the network of vessels, which resulted in a decrease of VA. 16 Uyama et al 13 reported that VA decreased in 24% (4/17) of the eyes treated with direct laser photocoagulation for PCV and that the visual outcomes in untreated eyes were better than those in treated eyes. These findings indicate that the visual function following the natural course of PCV or treatment with direct photocoagulation is poor.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] While its pathogenesis remains unclear, it is generally thought to be an inner choroidal vascular abnormality characterized by two main components: (1) a peculiar network of fine branching vessels external to choriocapillaris and (2) multiple terminal aneurysmal dilations at the border of the vascular network. These vascular dilations are sometimes visible clinically as a reddish-orange spheroidal polypoidal lesions, particularly if they are large enough and there is sufficient atrophy of the overlying retinal pigment epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]5 However, recent studies report that it also occurs in individuals of all races, ethnic groups, and sexes with a broad age range and that it appears to share similar characteristics with exudative age-related macular degeneration (AMD). 8,9,11,12,14 Within the expanded clinical spectrum of PCV, there is a possibility that some patients who were originally diagnosed with exudative AMD may actually have exudative maculopathy secondary to PCV rather than to AMD.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Indocyanine green angiography was useful in defining the deeply located choroidal lesions. Lafaut et al 6 diagnosed 14 of 374 eyes (4%) using indocyanine green angiography, presenting with occult choroidal neovascularisation, as PCV.…”
Section: Commentmentioning
confidence: 99%